Pengaruh Kepemilikan Manajerial dan Kepemilikan Institusional terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Pemoderasi - Mishell Shafira (2021)
This study aims to determine the effect of managerial ownership and institutional ownership on firm value with dividend policy as a moderating variable in 37 property and real estate companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research is a type of quantitative research using secondary data in the form of annual reports and company financial statements. Fixed Effect Model (FEM) with panel data regression was used in this study using STATA version 16. Based on the test results and analysis it can be concluded that managerial ownership has no effect on firm value, institutional ownership has no effect on firm value, dividend policy weakens ownership managerial effect on firm value, dividend policy cannot moderate institutional ownership on firm value, while the control variable, leverage has a significant effect on firm value and firm growth has no effect on firm value. The results of this study have implications for potential investors and regulators. Policy makers can use these findings, particularly on managerial ownership and institutional ownership, to increase firm value in Indonesia. Keywords: Managerial Ownership, Institutional Ownership, Dividend Policy, Firm Value, Leverage, and Company Growth.